Hydrophilicity/hydrophobicity of metal sulfide particles as a determinator of aggregation performance in wastewater. (April 2021) - Xia, Zhilin; Peng, Xianjia; Kong, Linghao; Hu, Xingyun
Graphical abstract: Highlights: Metal sulfide particles displays different aggregation performance in wastewater. Zeta potentials not explain the difference in particle aggregation performances. DFT calculation verified the hydrophilicity/hydrophobicity of the metal sulfides. Hydrophilicity/hydrophobicity determines aggregation behaviors of metal sulfides. Abstract: Differences in aggregation performance of metal sulfide particles generated in wastewater during sulfide precipitation processes cannot be adequately explained by their zeta potentials. Herein, different aggregation performances among CuS, CdS and As2 S3 particles produced by sulfide precipitation in strongly acidic wastewater were found to depend on the different hydrophilicity/hydrophobicity of these particles. Density functional theory (DFT) calculation revealed the mechanism of hydrophobicity/hydrophilicity of the metal sulfide particles, which verified the hydrophobic particles preferred to self-aggregate, whereas the hydrophilic particles were more likely to bind to H2 O molecules and disperse in wastewater. Metal sulfide particles generated under different conditions also have different hydrophilicity/hydrophobicity and on which the aggregation performances of the particles depend. It was confirmed that the different aggregation performances among CuS, CdS and ZnS particles generated in low-pH wastewater were also determined by their different hydrophilicity/hydrophobicity rather than their zeta potentials. This study explains the reason of different aggregation performances among precipitates produced by sulfide precipitation in wastewater. Additionally, this study has revealed that, in strongly acidic wastewater, the tiny and hydrophilic metal sulfide particles were difficult to be separated by settling and coagulation method, which provides an instruction to further study for the downstream separation process of the metal sulfide particles formed by sulfide precipitation.